2014
DOI: 10.4184/asj.2014.8.6.729
|View full text |Cite
|
Sign up to set email alerts
|

How Many High Risk Korean Patients with Osteopenia Could Overlook Treatment Eligibility?

Abstract: Study DesignRetrospective study.PurposeTo determine the prevalence of high risk patient with osteopenia requiring pharmacologic treatment and investigate the difference of 10-year fracture probability whether bone mineral density (BMD) include or not in Korean FRAX model.Overview of LiteratureMany people with the fracture have osteopenia rather than osteoporosis, and BMD alone could be considered as a chance to prevent fracture.MethodsThree hundred sixty-nine patients who was diagnosed as osteopenia were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Most of the patients were female (74.7%) and the Body Mass Index (BMI) was [23. 5 When we checked according to the treatment thresholds, 57 of 450 patients (12.7%) had a risk of major osteoporotic fracture ≥20% when calculated with BMD. 33 of 450 patients (7.3%) had a risk of major osteoporotic fracture ≥20% when the BMD is not used to calculate the value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients were female (74.7%) and the Body Mass Index (BMI) was [23. 5 When we checked according to the treatment thresholds, 57 of 450 patients (12.7%) had a risk of major osteoporotic fracture ≥20% when calculated with BMD. 33 of 450 patients (7.3%) had a risk of major osteoporotic fracture ≥20% when the BMD is not used to calculate the value.…”
Section: Resultsmentioning
confidence: 99%
“…With the popular use of FRAX ® , there is still a debate related to this tool without BMD information although the inclusion of BMD is optional [5,6]. However, another document found that including BMD in FRAX ® may greatly underestimate the risk [7].…”
Section: Introductionmentioning
confidence: 99%